Development of non-linear transfer functions for power amplifiers - Ooi, B.Z.M.; Lee, S.W.; Chung, B.K. (2011)
A behavioural-level model for non-linear power amplifiers is developed based on measured gain compression (AM-AM) and phase distortion (AM-PM) characteristics. The measured envelope-dependent gain compression component must be transformed to its instantaneous form for analysis. An improved method is proposed to perform this transformation using the measured 1 dB gain compression (P1 dB) and third-order intermodulation product (IP3) of a non-linear power amplifier. The authors also show that the phase distortion component depends only on the magnitude of the input signal and does not require a similar transformation. Using the proposed model, the simulated spectral regrowth and error vector magnitude (EVM) show a good match to the measured results of a 2.412 GHz Wireless Local Area Network (WLAN) GaAs field-effect transistor (FET) power amplifier.